2019
DOI: 10.1016/j.thromres.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps in thrombi retrieved during interventional treatment of ischemic arterial diseases

Abstract: Highlights-Neutrophil extracellular traps (NETs) modify the structure and stability of fibrin.-NET content of thrombi varies at different locations (brain, heart, peripheral arteries).-DNA and histones in thrombi correlate with age and systemic inflammatory markers.-The amount of fibrin is similar at all examined arterial locations.-Thicker fibrin fibers are formed in coronaries than in brain and peripheral arteries. 3 Abstract Introduction-The ultrastructure and cellular composition of thrombi has a profound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 51 publications
2
53
0
1
Order By: Relevance
“…Markers of NETs were previously detected at the site of thrombus formation and plaque rupture in different patient cohorts [8,[34][35][36] including patients with PAD [11]. However, our study is the first to show a significant association between surrogate markers of NET formation and ischemic outcomes in patients with stable PAD after infrainguinal angioplasty and stenting.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Markers of NETs were previously detected at the site of thrombus formation and plaque rupture in different patient cohorts [8,[34][35][36] including patients with PAD [11]. However, our study is the first to show a significant association between surrogate markers of NET formation and ischemic outcomes in patients with stable PAD after infrainguinal angioplasty and stenting.…”
Section: Discussionmentioning
confidence: 59%
“…Neutrophil extracellular traps (NETs) are DNA-and histone-containing structures released by neutrophils, and were originally shown to fight bacteria [5]. Recently, NETs and their components were identified in atherosclerotic plaques and arterial thrombi of mice and humans [6][7][8][9][10] as well as in thrombi of patients with PAD [11].…”
Section: Introductionmentioning
confidence: 99%
“…NETs are abundant in human venous thrombus samples, particularly those in the organizing stages [28]. Similarly, arterial thrombi from patients who suffered heart attack [29,30], stroke [31], or peripheral arterial disease [32] contain NETs (Fig. 1).…”
Section: Introductionmentioning
confidence: 98%
“…infusion of DNase interferes with thrombus formation (49,56). NETs are also enriched in human venous and arterial thrombi of patients who suffered from a heart attack (57), stroke (58), and peripheral vascular arterial occlusions (59). Furthermore, it has been shown that NETs alone are sufficient for vascular occlusions under septic conditions in the absence of host enzymes DNase1 and DNase1L3 (60) cleaves histones and interferes with their cytotoxic activity in a purified system, it had no effect on NETs-induced cytotoxicity suggesting that histone-dependent cytotoxicity is protected from APC degradation (63,64).…”
Section: Accepted Manuscriptmentioning
confidence: 99%